Multi-generation effects of lead (Pb) on two Daphnia species - de Araujo, Giuliana Seraphim; Ferreira, Abel Luís Gonçalves; da Maia Soares, Amadeu Mortágua Velho; Abessa, Denis Moledo de Souza [UNESP]; Loureiro, Susana (Springer Nature, 2024)
Two monophyletic Daphnia species (Daphnia magna and D. similis) were exposed to a sub-lethal concentration of Pb (50 µg/L) for nine generations under two food regimes (usual and restricted) and analyzed for acetylcholinesterase (AChE) activity, first reproduction delay, lifespan, and net reproductive rate (R0) at the subcellular, individual, and population levels, respectively. In the sixth generation, Pb-acclimated neonates were moved to clean media for three more generations to check for recovery. The net reproductive rate (R0) of D. magna was not affected by Pb. However, Pb stimulated reproduction, reduced lifespan, and decreased AChE activity. First reproduction delay and lifespan did not improve during the recovery process, suggesting a possible genetic adaptation. Food restriction reduced R0, lifespan, delayed hatching, and increased AChE activity; the opposite outcomes were observed for D. similis. The full recovery shown by R0 suggests the physiological acclimation of D. similis. Under food restriction, the animals exhibited a reduction of R0 and lifespan, delayed first reproduction, and increased AChE activity; however, there was no effect of Pb. The recovery process under food restriction showed that D. similis might not cope with Pb exposure, indicating a failed recovery. Such outcomes indicate that one model species’ sensitivity may not represent another’s sensitivity.
Keywords: Acetylcholinesterase; Lifespan; Multi-generation; Net reproductive rate (R0); Reproduction delay